2014
DOI: 10.1007/s10577-014-9433-9
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin-induced γH2AX foci map preferentially to replicating domains in CHO9 interphase nuclei

Abstract: Exposure to DNA damaging agents triggers phosphorylation of histone variant H2AX (generating γH2AX) in large chromatin regions flanking DNA lesions, allowing their immunodetection as nuclear foci. Even though a predominance of γH2AX foci in euchromatin has been postulated, foci positioning when DNA insult occurs in replicating eu- or heterochromatin regions has not been extensively explored. Labeling of interphase nuclei with 5-ethynyl-2'-deoxyuridine (EdU) pulses has revealed that DNA replication is temporari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
2
6
0
1
Order By: Relevance
“…Regarding their fluorescence intensity in the nucleus, the results indicated that, overall, the abundance of the three proteins augments after cell exposure to the DNA-damaging treatment comparatively to the control group ( Supplementary Figure S4A,C,E ), thus confirming the prior findings ( Figure 2 C, Figure 4 B and Figure 5 B). Focusing on the LAP1/γ-H2AX and TRF2/γ-H2AX immunocytochemistry experiments, two major γ-H2AX staining patterns were perceptible, comprising nuclei with discrete, countable foci and nuclei with pan-nuclear staining, which were more frequently encountered in cells cultured under normal conditions or in those incubated with bleomycin, respectively ( Figure 6 A and Figure 7 A), as formerly reported by others [ 59 ]. Interestingly, a careful visual examination of the microphotographs permitted the identification of multiple sites juxtaposed to the NE and in the nuclear interior where LAP1 staining overlaps with that of γ-H2AX, not only in bleomycin-treated cells but also in untreated ones that exhibited some degree of DNA damage ( Figure 6 A (arrowheads)).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Regarding their fluorescence intensity in the nucleus, the results indicated that, overall, the abundance of the three proteins augments after cell exposure to the DNA-damaging treatment comparatively to the control group ( Supplementary Figure S4A,C,E ), thus confirming the prior findings ( Figure 2 C, Figure 4 B and Figure 5 B). Focusing on the LAP1/γ-H2AX and TRF2/γ-H2AX immunocytochemistry experiments, two major γ-H2AX staining patterns were perceptible, comprising nuclei with discrete, countable foci and nuclei with pan-nuclear staining, which were more frequently encountered in cells cultured under normal conditions or in those incubated with bleomycin, respectively ( Figure 6 A and Figure 7 A), as formerly reported by others [ 59 ]. Interestingly, a careful visual examination of the microphotographs permitted the identification of multiple sites juxtaposed to the NE and in the nuclear interior where LAP1 staining overlaps with that of γ-H2AX, not only in bleomycin-treated cells but also in untreated ones that exhibited some degree of DNA damage ( Figure 6 A (arrowheads)).…”
Section: Resultssupporting
confidence: 77%
“…For this purpose, immunocytochemistry assays were performed to investigate the co-localization of endogenous LAP1, TRF2 and γ-H2AX in HeLa cells' nuclei in a baseline state and upon a short-term bleomycin exposure (200 µg/mL for 30 min, followed by 6 h of recovery). A general analysis by confocal microscopy revealed that all proteins are located at the expected nuclear compartments irrespective of the experimental condition, wherein γ-H2AX ( Figures 6A and 7A) and TRF2 ( Figures 7A and 8A) are typically dispersed across the nucleoplasm whereas LAP1 is mostly distributed throughout the NE (Figures 6A and 8A), being consistent with previous descriptions for each protein [18,22,44,59,60]. Regarding their fluorescence intensity in the nucleus, the results indicated that, overall, the abundance of the three proteins augments after cell exposure to the DNA-damaging treatment comparatively to the control group (Supplementary Figure S4A,C,E), thus confirming the prior findings ( Figures 2C, 4B and 5B).…”
Section: Lap1 and Trf2 Co-localize At The Nuclear Membrane And Intransupporting
confidence: 89%
“…Исходя из этих отправных моментов, синтезированы р21-МНТ EGF , которые содержали C-концевой фрагмент белка р21 (аминокислотные остатки 87-164) с участком, которым р21 связывается с PCNA [48]. ДНК повреждали блеомицином -противораковым агентом, вызывающим ее двухцепочечные разрывы [49], а для анализа повреждений ДНК и ее репарации использовали метод ДНК-комет в щелочной среде, позволяющий выявлять все типы разрывов ДНК. Предварительная инкубация клеток А431 с р21-МНТ EGF показала, что р21-МНТ EGF вызывают статистически значимое ингибирование репарации ДНК по сравнению с контрольными МНТ EGF , т.е.…”
Section: модульные нанотранспортерыunclassified
“…This pattern was irrespective of either different DNA concentrations or post-transfection incubation times (data not shown). Given the particular -catenin granule patterns observed, we characterized them by building three-dimensional (3D) models of the cell nuclei (Liddle et al, 2014). Thus, Z-stacks of the cells over-expressing -catenin WT or S646D were acquired and then 3D-models (see Figure 5C for reference) were constructed using software developed in the Interactive Data Language (IDL).…”
Section: Similar Transactivating Activity Of -Catenin Wild-type and mentioning
confidence: 99%
“…Z-stacks of single cells were obtained taking 10 images at a step size of 300 nm. The 3D-models of single nuclei were build using image-processing routines developed in SCIAN laboratory (www.scian.cl) based on interactive data language (IDL, ITT, Boulder, Colorado) as described in Liddle et al (2014). These routines included consecutive ROI segmentation stages, obtaining 3D-models of single nuclei and afterward granules, and finally quantification of their number, area and volume (Castañeda et al, 2014).…”
Section: Confocal Microscopy and 3d-modellingmentioning
confidence: 99%